Shell shock cinema : Weimar culture and the wounds of war - Kaes, Anton 1945- (Princeton Univ. Press, 2009)
The war at home. The wounded soldier -- The spirit of 1914 -- Film and nation -- The battle of images -- A medium for deception -- The new empire -- Mental breakdowns -- Tales from the asylum. War neurotics -- Recovering the past -- Phantoms and freaks -- From Dr. Charcot to Dr. Caligari -- Madness as resistance -- The Hitler connection -- Shattered space -- The return of the undead. The lost generation -- Mass death -- Dracula revisited -- A community under siege -- Hysteria on the home front -- The allure of the occult -- The work of mourning -- Myth, murder, and revenge. The national project -- Posing for Germany -- The will to form -- The fallen hero -- Excursus: Lang in World War I -- The sacred battle -- The end of violence -- The industrial battlefield. Rise of the machines -- Moloch war -- Lang's America -- The hunger for religion -- The workers' revolt -- Destruction and regeneration -- Aftershocks -- Conclusion